2015
DOI: 10.5505/tjtes.2015.43077
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of patients with blunt trauma and possible factors affecting mortality

Abstract: BACKGROUND:This study aimed to investigate the signs and prognosis of the patients hospitalized due to blunt trauma injuries and identify possible factors that affect mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…Accidental falls (low impact) accounted for 27.3% of the cases with assault and railway accidents responsible for the rest. Similar to other recent studies,[ 1 ] most of the patients in our study were between 21 and 40 years of age. The mortality in patients >50 years was 13.25% as against 9% in those below 50 years of age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Accidental falls (low impact) accounted for 27.3% of the cases with assault and railway accidents responsible for the rest. Similar to other recent studies,[ 1 ] most of the patients in our study were between 21 and 40 years of age. The mortality in patients >50 years was 13.25% as against 9% in those below 50 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…found hemodynamic instability and need for transfusion to be reliable predictors of mortality in all trauma patients. [ 1 ] A low GCS due to underlying head injury cannot be modified except through the management of head injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This imbalance was largely due to inclusion criteria being met at a lower rate among women than men (most commonly due to anemia) and to women being less willing to donate blood for reasons such as breastfeeding. However, studies involving actual patients with trauma have also involved higher numbers of male patients than female patients …”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of blunt abdominal trauma is 90%. [7] Ozpek et al [8] have reported the most frequent causes of blunt abdominal trauma as motor vehicle accidents in 62% and fall from heights as 27% of the cases. Mortality is seen in nearly 10% of the cases.…”
Section: Introductionmentioning
confidence: 99%